2009
DOI: 10.1055/s-0029-1185903
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Defatted Sesame Seeds Extract againstin vitroandin vivoIschemic Neuronal Damage

Abstract: Sesame (Sesamum indicum L.) is an important oilseed crop that possesses a wide spectrum of pharmacological activities. Many studies have been conducted to investigate its health-promoting effects. Compared to other plant oils, sesame seed oil is highly stable to oxidation and has been demonstrated to have protective effects against ischemia-reperfusion injury in the rat brain. However; the effects of defatted sesame seeds extract (DSE) have not been studied yet. The purpose of this study was to evaluate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
(39 reference statements)
1
17
0
1
Order By: Relevance
“…It is also consistent with the sesamin antioxidant effect that protects hypoxia-or H 2 O 2 -induced PC12 cell injury [22]. A study with defatted sesame seeds extract (30, 100 and 300 mg/kg) given twice orally at 0 h and 2 h after onset of ischemia shows the reduction of brain infarct volume dose-dependently and improves sensory-motor function [34]. Thus, suppression of KA-induced ROS and Ca 2+ release by sesamin was consistent with these notions.…”
Section: Discussionsupporting
confidence: 62%
“…It is also consistent with the sesamin antioxidant effect that protects hypoxia-or H 2 O 2 -induced PC12 cell injury [22]. A study with defatted sesame seeds extract (30, 100 and 300 mg/kg) given twice orally at 0 h and 2 h after onset of ischemia shows the reduction of brain infarct volume dose-dependently and improves sensory-motor function [34]. Thus, suppression of KA-induced ROS and Ca 2+ release by sesamin was consistent with these notions.…”
Section: Discussionsupporting
confidence: 62%
“…Studies have shown that antioxidant compounds inhibit JNK MAPK activation in microglia represent potential anti-inflammatory effects and protect neurons damage [5,20,21]. In addition, antioxidant compounds inhibit JNK MAPK activation in neuron and cardiomyocyte cells represent potential protective effects from hypoxic damage [5,22-24]. Sesamin can regulate microglial activities by inhibition of the intracerebral hemorrhage-induced p44/42 MAPK pathway and protect neuronal cells by inhibition of hypoxia-induced ERK, JNK, p38 MAPK [5,25].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to brain diseases, sesaminol glucoside, one of the components of the extract, was reported to have protective effects in Alzheimer disease models (Um et al , ). In a previous study, the neuroprotective effects of defatted sesame extract (DSE) and the mechanisms of action in ischaemia models were also reported (Jamarkattel‐Pandit et al , ).…”
Section: Introductionmentioning
confidence: 99%